Palaeomagnetism of Bahariya iron ores and their genetic implications, North Western Desert, Egypt. Issue 1 (2nd January 2019) - Awad, A.; Khashaba, A.; Abdel Aal, E.; El-Shayeb, H.; Khalil, A.; El-Hemaly, I.; Mostafa, R.
ABSTRACT: Integrated rock magnetic, palaeomagnetic and magnetic fabric studies have been carried out, in order to rely a better understanding of the age and origin of the Bahariya iron ores. A total of 80 oriented block samples were collected from 10 sites covering the three iron mining areas at Bahariya Oasis (El Gedida, Ghorabi and El Harra) within an area located between latitudes (28° 24` to 28° 29`N) and longitudes (29° 02` to 29° 11`E). Rock magnetic measurements reveal that, the main magnetic carrier is the haematite. Goethite and pyrrhotite, that are also present as subordinate constituents in the studied samples. Careful thermal demagnetization successfully enabled the isolation of the characteristic remanent magnetization of primary origin, which yields a magnetic position at Lat. 75.3º N and Long. 137.9º E revealing that, both the ore and host rocks are of the same age. Magnetic fabric studies on these ores indicated that, they are still holding their primary Fabrics of sedimentary origin.